HCRP1 expression status is a significant prognostic marker in oral and oropharyngeal cancer. (14th August 2012) - Perisanidis, C; Savarese‐Brenner, B; Würger, T; Wrba, F; Huynh, A; Schopper, C; Kornek, G; Selzer, E; Ewers, R; Psyrri, A; Krainer, M; Filipits, M
<x xml:space="preserve">Abstract</x> Objective The hepatocellular carcinoma‐related protein 1 (HCRP1) is a key factor in the degradation of the epidermal growth factor receptor. In this study, we assessed the prognostic significance of HCRP1 expression in patients with oral and oropharyngeal squamous cell carcinoma (OOSCC). Methods HCRP1 expression was determined by immunohistochemistry on tissue biopsy sections of 111 patients with locally advanced OOSCC undergoing neoadjuvant chemoradiotherapy followed by surgery. The Kaplan–Meier method and Cox regression models were used for survival analyses. Results Low HCRP1 expression was associated with poor recurrence‐free survival (P = 0.046) and overall survival (P = 0.03). Multivariate analysis revealed that low HCRP1 expression remained an independent risk factor for relapse (HR 2.98, 95% CI 1.19–7.49, P = 0.02) and death (HR 3.04, 95% CI 1.19–7.79, P = 0.02). Conclusion Low HCRP1 expression was found to be of adverse prognostic significance in patients with OOSCC who received preoperative chemoradiotherapy.